Biochemical characterization of a low molecular weight aspartic protease inhibitor from thermo-tolerant bacillus licheniformis: kinetic interactions with pepsin - Kumar, Ajit; Rao, Mala (Biochimica et Biophysica Acta-General Subjects, 2006)
The present article reports a low molecular weight aspartic protease inhibitor, API, from a newly isolated thermo-tolerant Bacillus licheniformis. The inhibitor was purified to homogeneity as shown by rp-HPLC and SDS-PAGE. API is found to be stable over a broad pH range of 2-11 and at temperature 90 degrees C for 2 1/2 h. It has a Mr (relative molecular mass) of 1363 Da as shown by MALDI-TOF spectra and 1358 Da as analyzed by SDS-PAGE The amino acid analysis of the peptide shows the presence of 12 amino acid residues having Mr of 1425Da. The secondary structure of API as analyzed by the CD spectra showed 7% alpha-helix, 49% beta-sheet and 44% aperiodic structure. The Kinetic studies of Pepsin-API interactions reveal that API is a slow-tight binding competitive inhibitor with the IC(50) and K(i) values 4.0nM and (3.83 nM - 5.31 nM) respectively. The overall inhibition constant K(i)* value is 0.107 +/- 0.015 nM. The progress curves are time-dependent and consistent with slow-tight binding inhibition: E+I reversible arrow (k(4), k(5)) EI reversible arrow (k(6), k(7)) EI*. Rate constant k(6) = 2.73 +/- 0.32 s(-1) reveals a fast isomerization of enzyme-inhibitor complex and very slow dissociation as proved by k(7)=0.068 +/- 0.009s(-1). The Rate constants from the intrinsic tryptophanyl fluorescence data is in agreement with those obtained from the kinetic analysis; therefore, the induced conformational changes were correlated to the isomerization of EI to EI*. (c) 2006 Elsevier B.V. Ail rights reserved.
Keywords: Aspartic protease inhibitor; Bacillus licheniformis; enzyme kinetic; Pepsin; Slow-tight binding inhibition

Novel bifunctional peptidic aspartic protease inhibitor inhibits chitinase A from Serratia marcescens: kinetic analysis of inhibition and binding affinity - Kumar, Ajit; Rao, Mala (Biochimica Et Biophysica Acta-General Subjects, 2010)
Background: Chitinase inhibitors have chemotherapeutic potential as fungicides, pesticides and antiasthmatics. The majority of chitinase inhibitors reported are natural products like argifin, argifin linear fragments, argadin, allosamidin and disulfide-cyclized peptides. Here, we report a novel peptidic inhibitor API (Aspartic Protease Inhibitor), isolated from Bacillus licheniforrnis that inhibits chitinase A (ChiA) from Serratia marcescens. Methods: The binding affinity of API with ChiA and type of inhibition was determined by the inhibition kinetics assays. Fluorescence and CD spectroscopic analysis and chemical modification of API with different affinity reagents elucidated the mechanism of binding of API with ChiA. Results and conclusions: The peptide has an amino acid sequence N-Ile(1)-Cys(2)-Glu(3)-Ala(4)-Glu(5)-His(6)-Lys(7)-Trp(8)-Gly(9)-Asp(10) -Tyr(11)-Leu(12)-Asp(13)-C. The ChiA-API kinetic interactions reveal noncompetitive, irreversible and tight binding nature of API with I-50= 600 nM and K-i = 510 nM in the presence of chromogenic substrate pnitrophenyl-N,N'-diacetyl-beta-chitobioside[p-NP-(GIcNAc)(2)]. The inhibition progress curves show a two-step slow tight binding inhibition mechanism with the rate constant k(5) = 8.7 +/- 1 x 10(-3) s(-1) and k(6) = 7.3 +/- 0.6 x 10(-5) s(-1). CD-spectra and tryptophanyl fluorescence analysis of ChiA incubated with increasing API concentrations confirms conformational changes in enzyme structure which may be due to irreversible denaturation of enzyme upon binding of API. Chemical modifications by WRK abolished the anti-chitinase activity of API and revealed the involvement of carboxyl groups in the enzyme inactivation. Abolished isoindole fluorescence of OPTA-labeled ChiA demonstrates the irreversible denaturation of ChiA upon incubation with API for prolonged time and distortion of active site of the enzyme. General significance: The data provide useful information that could lead to the generation of drug-like, natural product-based chitinase inhibitors. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Aspartic protease inhibitor; Bacillus licheniformis; Chitinase A; Enzyme kinetics; Slow tight binding inhibition

Development of an in silico platform (TRIPinRNA) for the identification of novel RNA intramolecular triple helices and their validation using biophysical techniques - Rakheja, Isha; Bharti, Vishal; Sahana, S.; Das, Prosad Kumar; Ranjan, Gyan; Kumar, Ajit; Jain, Niyati; Maiti, Souvik (Biochemistry, 2024)
There are surprisingly few RNA intramolecular triple helices known in the human transcriptome. The structure has been most well-studied as a stability-element at the 3 ` end of lncRNAs such as MALAT1 and NEAT1, but the intrigue remains whether it is indeed as rare as it is understood to be or just waiting for a closer look from a new vantage point. TRIPinRNA, our Python-based in silico platform, allows for a comprehensive sequence-pattern search for potential triplex formation in the human transcriptome-noncoding as well as coding. Using this tool, we report the putative occurrence of homopyrimidine type (canonical) triple helices as well as heteropurine-pyrimidine strand type (noncanonical) triple helices in the human transcriptome and validate the formation of both types of triplexes using biophysical approaches. We find that the occurrence of triplex structures has a strong correlation with local GC content, which might be influencing their formation. By employing a search that encompasses both canonical and noncanonical triplex structures across the human transcriptome, this study enriches the understanding of RNA biology. Lastly, TRIPinRNA can be utilized in finding triplex structures for any organism with an annotated transcriptome.